(untitled) (Sebha University Conference Proceedings, 2024)
This study aimed to investigate the impact of auditors’ tacit knowledge dimensions (skill, experience, thinking) on electronic banking operations risk management. The descriptive-analytical method was employed, and a simple random sample of Sudanese banks (Faisal, Khartoum, Omdurman National) was chosen as the study sample, consisting of 70 respondents. A questionnaire was used as a data collection tool. The results indicated a significant interest in electronic operations risk management in Sudanese banks. There was a statistically significant impact of the combined dimensions of auditors’ tacit knowledge and each dimension separately on electronic banking operations risk management in Sudanese banks. The study recommended the necessity of continuous improvement in performance and the development of policies and procedures to maintain a high level of electronic security in Sudanese banks. It also emphasized the importance of investing in the development of training and continuous education programs for auditors to enhance their tacit knowledge in the field of electronic banking operations risk management and guide them towards best practices.